Innovative Extraction Techniques and Hyphenated Instrument Configuration for Complex Matrices Analysis - Locatelli, Marcello (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The present Special Issue, "Innovative Extraction Techniques and Hyphenated Instrument Configuration for Complex Matrices Analysis", aims to collect and to disseminate some of the most significant and recent contributions in the interdisciplinary area of innovative extraction procedures from complex matrices followed by validated analytical methods using hyphenated instrument configurations to support the optimization of the whole process and the scale-up possibility